Apakah Religiusitas sebagai Faktor Penarik Terhadap Kepuasan Nasabah (Studi Kasus BMT Idrisiyyah Tasikmalaya) - Dede Aji Mardani; Riska Gunawati (Universitas Mataram, 2020)
The purpose of this study is to know and analyze the implementation of services, perceptions of religiosity of institutions and customer satisfaction, as well as the influence of service quality and religiosity perceptions in BMT Idrisiyyah to customer satisfaction BMT Idrisiyyah Tasikmalaya.The research method used in this research is the field research method (field reaserch), while the data collection techniques are done through the spread of questionnaires and interviews. The sampling technique using slovin formula with the number of respondents 100 customers and the analysis tools used are classical assumption test, multiple linear regression analysis, coefficient of determination test, t-test and F test.Based on the results of research and F-test results (simultaneous) showed that service and perceptions of religiosity together affect the customer satisfaction. The result of t-test (partial) which have positive effect significantly to customer satisfaction from service quality is variable of reliability, responsiveness variable, assurance variable and empathy while for physical proof (tangible) has no effect to customer satisfaction. For the perception variable religiosity also does not affect customer satisfaction. For the mutual influence of service quality and religiosity perception have an effect on customer satisfaction in BMT Idrsiyyah with significance value 0,000 and F value equal to 6,750.